Stability of Encapsulated Vitamin C in Modified Cassava Flour (MOCAF)-Based Composite Noodles - Resti Pranata Putri; Nadiyah Zuhroh; Nadhifah Al Indis; Annisa'U Choirun; Amellia Dwi Rizkyana (Jurnal Biologi Tropis, 2026)
This study evaluated the effect of Modified Cassava Flour (MOCAF) substitution on the stability of encapsulated vitamin C (ascorbic acid), crude fiber content, and color index of starch-based composite noodles. Vitamin C was encapsulated using a maltodextrin–CMC matrix (18.2:1.8%) via freeze-drying and incorporated into noodles with varying wheat-to-MOCAF ratios: MCF00 (100:0), MCF01 (90:10), MCF02 (70:30), and MCF03 (50:50). These were compared with Control 1 (unfortified) and Control 2 (fortified with non-encapsulated vitamin C). Encapsulation significantly improved vitamin C retention, reaching 0.32–0.38 mg/g, approximately twofold higher than the non-encapsulated control (0.15 mg/g). Thermal processing caused a marked decline in the Modified Noodle Color Index (NCIm) of Control 2 (62.67 to 51.44), likely due to Maillard-like browning reactions. In contrast, noodles with encapsulated vitamin C maintained a stable color (NCIm 61.06 to 63.44). Increasing MOCAF substitution significantly enhanced crude fiber content (up to 4.97% in MCF03) and improved noodle lightness (L*). Overall, the maltodextrin–CMC system effectively protected vitamin C from thermal degradation, regardless of starch matrix variation. Further studies are recommended to investigate shelf-life stability and in vitro release of vitamin C in the gastrointestinal tract.